2013
DOI: 10.1002/pbc.24488
|View full text |Cite
|
Sign up to set email alerts
|

Survival following disease recurrence of primary localized alveolar rhabdomyosarcoma

Abstract: Post-relapse survival for primary localized RMA is generally poor. However, certain patient groups differed significantly in their likelihood of survival and 50% of patients with circumscribed relapses treated with ALRT survived. These findings may form the basis for an evidence-based risk-stratification for recurrent disease including relapse treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…We speculated that after events, salvage RT took the place of initial RT and became a high-weight prognostic factor, and this speculation was supported by our results that salvage RT was a statistically significant prognostic factor for OS in patients with events. It's reported that adequate local therapy is an important factor for survival after relapse [29], RT can further improve OS in relapsed patients undergone a repeat surgery [30], and local treatment such as RT and repeat surgery should be systemically considered even in previously irradiated patients [31]. The cure of parameningeal RMS is unlikely without RT [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that after events, salvage RT took the place of initial RT and became a high-weight prognostic factor, and this speculation was supported by our results that salvage RT was a statistically significant prognostic factor for OS in patients with events. It's reported that adequate local therapy is an important factor for survival after relapse [29], RT can further improve OS in relapsed patients undergone a repeat surgery [30], and local treatment such as RT and repeat surgery should be systemically considered even in previously irradiated patients [31]. The cure of parameningeal RMS is unlikely without RT [11].…”
Section: Discussionmentioning
confidence: 99%
“…These patients' survival is affected by many factors and some of them may be higher-weight prognostic factors, such as tumor size, primary site, regional nodal involvement, metastasis, repeat surgery, previous chemo and RT plan, multi-relapse, etc. [3,19,27,29,32]. All these factors make salvage RT unlikely to be an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Three-year survival after relapse is approximately 37%, and it is associated with several factors such as histology, the initial tumor site, the pattern of relapse (local or metastatic), and prior radiotherapy. [4][5][6][7][8] The recommended surveillance after treatment, according to the European Paediatric Soft Tissue Sarcoma Study Group Rhabdomyosarcoma 2005 (EpSSG-RMS 2005) protocol, includes a clinical examination together with a magnetic resonance imaging (MRI) or computed tomography (CT) scan of the primary tumor site and a chest x-ray, which should be performed every 3 months in the first year and every 4 months in the second and third years after treatment. The recommended surveillance is once a year in the fourth and fifth years after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with disease progression respond poorly to the initial treatment, and primary tumor enlargement, local invasion, regional nodal involvement, and even metastasis can be anticipated. Disease relapse represents late treatment failure [19,20], which means recurrence of RMS in any form after last treatment during off therapy surveillance. Patients with disease relapse usually respond well to the initial treatment and end with complete remission.…”
Section: Discussionmentioning
confidence: 99%